If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(2x + 5) = -5(1 + 4x) Reorder the terms: -7(5 + 2x) = -5(1 + 4x) (5 * -7 + 2x * -7) = -5(1 + 4x) (-35 + -14x) = -5(1 + 4x) -35 + -14x = (1 * -5 + 4x * -5) -35 + -14x = (-5 + -20x) Solving -35 + -14x = -5 + -20x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '20x' to each side of the equation. -35 + -14x + 20x = -5 + -20x + 20x Combine like terms: -14x + 20x = 6x -35 + 6x = -5 + -20x + 20x Combine like terms: -20x + 20x = 0 -35 + 6x = -5 + 0 -35 + 6x = -5 Add '35' to each side of the equation. -35 + 35 + 6x = -5 + 35 Combine like terms: -35 + 35 = 0 0 + 6x = -5 + 35 6x = -5 + 35 Combine like terms: -5 + 35 = 30 6x = 30 Divide each side by '6'. x = 5 Simplifying x = 5
| -17x-25=19-15x | | 14x+x+x+4+(-6)=14x+x+x+4-6 | | 0=9x+81 | | 7+4x-1=12 | | 3(2x-1)-6x=-4 | | 8(n-2)-3(n-4)=6(n-7)+8 | | 3x-7=3x+13 | | -6(4x-2)=-24x+12 | | 1/4(4q+12)=2+18-3q | | 0.25+4.75=6 | | -12+21=-3 | | 18x+9y=360 | | 4x-11=-23 | | 3(2x-4)=21 | | 2x-4+0.5(2+8x)=0 | | 36-11=5(x-4) | | 33+3y-12=12y-9-4y | | -1y-22-1y=-16 | | 15=-3(n-4) | | x^2+26x+112=0 | | x+20+4x=-33-4x-37 | | 6x-6=10x+15-15 | | 5-(3)= | | 48f+6.4=-8.48 | | 10y+9=-3 | | 2(-2x+4)=8 | | -4(2x-3)-3-8x=-11 | | 24-6k=6[4-k] | | 10+45u= | | a+140=a+0.05a | | 15-6x+7-3x= | | -16+6=-6r+2 |